2021
DOI: 10.15376/biores.16.4.8006-8021
|View full text |Cite
|
Sign up to set email alerts
|

Wood-based boards mechanical properties and their effects on the cutting process during shredding

Abstract: In order to design effective shredding machines dedicated to shredding wood-based waste, information about the mechanical properties of materials subjected to shredding is necessary. A number of mechanical properties of particleboard, oriented strand boards, and medium-density fibreboards in the aspect of shredding process have been experimentally determined in the article. The influence of material type, blade geometries, and cutting depth on cutting force and elasticity coefficient were analysed. Blade geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It can be found that the cutting power is negatively correlated with the rake angle, but positively correlated with other three factors, including cutting speed, depth of cut, and flank wear. In related work, with the aim of exploring the wood-based panel's mechanical properties during shredding, the cutting and elasticity coefficients with particle board, oriented strand boards, and medium-density fiberboard were explored by Kukla and Wargula [27] at different cutting conditions of blade geometries and cutting Forests 2022, 13, 1397 6 of 11 depth. In the selected cutting parameters, cutting depth plays a crucial positive role in affecting the cutting force.…”
Section: Influence Of Cutting Conditions On Cutting Powermentioning
confidence: 99%
“…It can be found that the cutting power is negatively correlated with the rake angle, but positively correlated with other three factors, including cutting speed, depth of cut, and flank wear. In related work, with the aim of exploring the wood-based panel's mechanical properties during shredding, the cutting and elasticity coefficients with particle board, oriented strand boards, and medium-density fiberboard were explored by Kukla and Wargula [27] at different cutting conditions of blade geometries and cutting Forests 2022, 13, 1397 6 of 11 depth. In the selected cutting parameters, cutting depth plays a crucial positive role in affecting the cutting force.…”
Section: Influence Of Cutting Conditions On Cutting Powermentioning
confidence: 99%
“…Medium-density fiberboards are produced from a series of lignocellulosic fibers, following a thermal and mechanical process of defibration that uses the combined action of heat with mechanical energy to break the bonds between cells [6,23]. Depending on the manufacturing process of MDF, fibers with a high degree of fibrilization are used for the wet process, and long and thin fibers are used for the dry process [9,[25][26][27][28][29][30][31]. To obtain MDF, small-diameter fibers are used, so that a degree of compressibility is achieved without additional energy consumption [29].…”
Section: Introductionmentioning
confidence: 99%